Structure and properties of AlMgSi alloys after ECAP and POST-ECAP ageing - Fujda, Martin (Materiali in tehnologije, 2012)
The mechanical properties and the microstructures of the EN AW 6082 and EN AW 6063 aluminium alloys subjected to pre-ECAP solutionizing heat treatment, equal channel angular pressing (ECAP), and post-ECAP artificial ageing are compared. The quenched alloy states were severely deformed at room temperature by the ECAP technique following route BC. Repetitive ECAP caused formation of the ultra-fine subgrain microstructure with a high dislocation density and high strain hardening of the alloys, thus exhibiting an improvement in strength, but also a degradation of the analysed alloys' ductility. The application of the optimal artificial-ageing regimes after a severe plastic deformation improved only the tensile ductility of the alloys, while their strength was slightly decreased because the softening effect caused by the solid-solution recovery and the relaxation of the internal stress dominated over the hardening effect caused by the expected metastable b''- and b'-Mg2Si phase precipitation during the artificial ageing treatment.
Keywords: aluminijeve zlitine; aluminium alloy; aluminium alloys; ECAP ageing; stiskanje; pressing; staranje; microstructure; mikrostruktura; mechanical properties; mehanske lastnosti